Analysis of Seaweed Chips Business Feasibility (Case Study on "NORIbet" Seaweed Processed MSMEs in the City of Bandung, West Java) - Ristiafani; Ine Maulina; Emma Rochima; Iwang Gumilar (Grouper, 2025)
Indonesia is the world’s largest producer of seaweed, contributing 16.2% to the global market, yet most of its seaweed is still exported in raw form. This limits added value creation and hinders the growth of micro, small, and medium enterprises (MSMEs). NORIbet, a seaweed-processed MSME based in Bandung, West Java, aims to address this gap by developing value-added seaweed products. However, the business still faces challenges in cost management, marketing, and technology access. This research was conducted from June to October 2024 to analyze NORIbet's business profile using the Business Model Canvas (BMC) and evaluate its financial feasibility. A descriptive case study approach combining qualitative and quantitative methods was used, with data collected through observations and interviews involving two business owners and two production staff, selected using purposive sampling. Financial feasibility was analyzed through indicators such as profit, revenue cost ratio (R/C), break even point (BEP), payback periods (PP), and sensitivity analysis. Findings indicate that NORIbet successfully implements the 9 BMC elements in a well-structured manner. The business earned an annual profit of IDR 766,334,100 with a profitability rate of 56.1% and an R/C ratio of 2.28. Payback period is estimated at 4.6 months, and each product packaging type has its own BEP unit. Sensitivity analysis showed that a 10% increase in cost reduced profitability to 51.7%, while a 10% cost reduction increased it to 60%, indicating strong cost efficiency and operational resilience. These results confirm that NORIbet is highly feasible and has strong development potential.